The Transparency of School Operational Assistance (SOA) Fund Management at MTs Ummusabri of Kendari - Rahim, Titin Rahmiatin; , Prof. Dr. Sutama, M.Pd; , Dr. Phil. Dewi Candraningrum, M.Ed (2013)
There were three objectives of this study. The first was to describe the clarity roles and responsibilities of SOA fund management team at MTs Ummusabri of Kendari. The second is to describe the process of planning, implementation, and reporting of SOA fund. Finally, this study is aimed to describe the control (monitor and evaluation) from the stake holders towards the SOA fund management. It was a qualitative research using ethnography design. Methods of data collection used were observation, interviews and documentation. Data analysis was started by collecting the data, reducing data, presenting data, and drawing conclusion. Test of data validity used credibility, transferrability, confirmability and dependability. The research revealed three main findings, namely (1) The roles and responsibilities of SOA fund management team at MTs Ummusabri of Kendari was established in a clear ways eventhough the roles and responsibilities of SOA fund management team were mostly submitted to the treasurer's hand as the absence of SOA fund management team officially. Although the involvement of stakeholders in the SOA fund management team was fairly small but all duties and responsibilities of the management of SOA fund run smoothly and effectively. (2) The process of planning, implementation and reporting of SOA fund management at MTs Ummusabri of Kendari was arranged in the detailed form of budgets and spending plans of Madrasah (BSPM) based on the priority scale. The use of the SOA fund in MTs Pesri refers to BRPM set by the management team of the SOA fund, which is consist of the treasurer, principal and approved by the council board of madrasah. The implementation of the SOA fund in MTs Pesri is based on the guidelines of the minister of education and culture of Indonesia number 76 on the technical manual use of the funds. The spending report of SOA funds is prepared and signed by the treasurer in the form of SOA fund accountability report quarter I, II, and III. These reports were acknowledged by the principal and the school committee. (3) The control (monitoring and evaluation) from the stake holders towards school operational Assistance (SOA) fund management was performed by two ways namely internal and external monitoring. The Control of the SOA fund used was involved the MTs Pesri principal (internal monitoring) and from another department such as SAA, Ministry of Education and Religious Department (external monitoring). The monitoring was only performed at the stage of implementation of SOA fund and it just merely controls the documents or statements, so that the control lack of a sustainable control.